Feasible Researches in Historical Jesus Tradition: A Critical Response to Chris Keith - Downing, Francis Gerald (Journal for the study of the New Testament, 2017)
In his programmatic article, The Narratives of the Gospels and the Historical Jesus: Current Debates, Prior Debates, and the Goal of Historical Jesus Research', Chris Keith argues for a very clear distinction between two styles or types of historiography (Keith 2016). One searches behind' the gospel texts for authentic' matter; the other, according to Keith, the only feasible' method, allowing for memory theory' in particular, is to discern how the tradition' developed, and only thence generate theoretical reconstructions of a Jesus who may have originally prompted it. It is argued here that this presents an unsustainable dichotomy, for the historical tradition(s) of the ?rst Christians also themselves lie behind' our texts, and imaginative searches for both Jesus and Jesus traditions have to proceed hand in hand.